Do government support correlates enhance financial performance? Rural microenterprises perspectives - Nkote, Isaac; Jakweyo, Christopher (Emerald, 2024)
Purpose The purpose of this study was to examine the determinants of financial performance of the rural microenterprises, with microcredit access as the mediating variable. Design/methodology/approach A survey using a self-administered questionnaire to the managers/owners of the rural microenterprises was adopted. The data was collected on the three study variables; financial literacy, credit access and financial performance. A total of 148 fully completed and useable questionnaires were used in the analysis. The researchers performed factor analysis, correlations, regression and mediation analysis to test the hypotheses. Findings The study revealed the existence of a statistically significant and positive relationship between financial literacy and microcredit access, microcredit access and financial performance. On the other hand the financial literacy had a significant but negative impact on the financial performance of the rural microenterprises. In the final analysis, financial literacy is only effective in impacting financial performance when mediated by microcredit access. We conclude that policies that emphasize financial literacy are ineffective in fostering the financial performance and growth of the microenterprises. Originality/value The study is original as it addresses the combined effect of credit rationing and resource based view theories to explain the financial performance of informal rural microenterprises that are the key livilihood business undertaking in many developing countries.